On the long-term fatigue assessment of mooring and riser systems - Low, Ying Min (2013)
Mooring lines and risers are exposed to numerous sea states during its service life, thus a fatigue assessment should account for the long-term wave condition which is typically represented by the joint statistics of the significant waveheight and a characteristic period. Since it is unfeasible to consider all possible sea states, a common practice, as recommended by design codes, is the lumping of sea states into blocks. However, there are neither guidelines nor consensus on an effective blocking strategy, and the level of discrepancy arising from blocking has not been investigated. In fact, the present problem can be treated by a variety of techniques that are fairly standard within the specialist field of uncertainty analysis, but these methods are foreign to many practicing engineers. Therefore, this paper seeks to make the methodology accessible to the wider offshore engineering community. Six existing approaches are implemented on an illustrative floating system and evaluated for accuracy and efficiency. This paper also presents a novel customized approach that is fast and precise. The approach adopts a multi-peaked third-order asymptotic approximation that is rarely seen in the literature. The peaks are located by a tailored optimization algorithm that exploits the problem peculiarities.